ANALISIS KEBIJAKAN PENGEMBANGAN WISATA BAHARI PANTAI MARINA TAHUN 2010 - 2015 - Zaki, Muhammad Fachri; Pujiati, Amin (Efficient: Indonesian Journal of Development Economics, 2018)
Nautical tourism according to Hidayat (2000: 15) are activities related to marine which includes relaxing on the beach or enjoying the natural surroundings, swimming, surfing, diving, water sky and touring around, or in other words all the potential economic value that can be utilized to increase the income of the surrounding communities and increase state revenues. The purpose of this study was to determine the development undertaken by the Government of the city, to find out the sale of the City and to determine the role of the community in supporting marine tourism activities Beach Marina. This research is located in the Marina Beach of Semarang as has been defined as marine tourism area in the city of Semarang. This research uses descriptive qualitative data analysis techniques including data collection, data reduction, data presentation and decision making. This study uses descriptive qualitative research and quantitative descriptive. The conclusion of this study is the development undertaken by the Tourism Department of Semarang and manager of the Marina include a variety of development, promotion conducted on marine tourism Marina Beach include promotion in tourism events with regional and national scale, in cooperation with the stations, local TV, the role of the public against marine tourism Semarang inclined slightly for the management of Marina handed over to private parties. Wisata bahari menurut Hidayat (2000:15) adalah aktivitas yang berkaitan dengan kelautan yang meliputi santai di pantai atau menikmati alam sekitar, berenang, surfing, diving, water sky dan tur keliling, atau dengan kata lain segala potensi yang mempunyai nilai ekonomi sehingga dapat dimanfaatkan untuk meningkatkan pendapatan masyarakat sekitar serta meningkatkan pendapatan negara. Tujuan Penelitian ini untuk mengetahui pembangunan yang dilakukan oleh Pemerintah Kota Semarang, untuk mengetahui promosi dari Pemerintah Kota dan untuk mengetahui peran masyarakat dalam mendukung kegiatan wisata bahari Pantai Marina. Penelitian ini berlokasi di kawasan Pantai Marina Kota Semarang sebagaimana telah ditetapkan sebagai kawasan wisata bahari di Kota Semarang. Penelitian ini menggunakan teknik analisis data deskriptif kualitatif meliputi pengumpulan data, reduksi data, penyajian data dan pengambilan keputusan. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dan deskriptif kuantitatif. Kesimpulan dari penelitian ini adalah pembangunan yang dilakukan oleh Dinas Pariwisata Kota Semarang dan pengelola terhadap Pantai Marina meliputi berbagai pembangunan, promosi yang dilakukan terhadap wisata bahari Pantai Marina meliputi promosi di event wisata dengan skala regional maupun nasional, bekerjasama dengan statisun tv lokal, peran masyarakat terhadap wisata bahari Kota Semarang cenderung sedikit karena pengelolaan Pantai Marina diserahkan kepada pihak swasta.